The return of YHWH : the tension between deliverance and repentance in Isaiah 40-55 - Scheuer, Blaženka (Walter de Gruyter, 2008)
The theology of Isaiah 40-55 has two seemingly contradictory aspects: the tension between the consolatory message of deliverance, and the harsh tone of accusation and the call to repentance. This study argues that such tension does not necessarily disclose a different authorship, but that it expresses the basic nature of the relationship between YHWH and the Israelites, in which the actions of YHWH and the actions of the people stand in a relationship of interdependence. Such interdependence is essential for the re-establishment and the continued existence of the relationship between YHWH and.
Keywords: Bible. -- Isaiah, XL-LV -- Criticism, interpretation, etc.; Bible. -- Isaiah, XL-LV; Repentance.; Repentir.; RELIGION -- Biblical Studies -- Prophets.; Repentance; Criticism, interpretation, etc.